Analysis Of Community Participation In The Development Of Bromonilan Village Tourism - Yunita, Wiwik; Mahendra, Gerry Katon (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Tourist Village Bromonilan is village tour based nature and culture that have including in category village tour sustainable development in Sleman Regency . Research This using 4 indicators participation , which consists of from taking decision , implementation activity or programs created , monitoring evaluation and utilization results . The method used in the research This is approach qualitative in nature descriptive . Research result show that village tour Bromonilan in Sleman Regency has sufficient participation Good in development village tourism , development village tour Already effective However there is obstacle related in method manage village , taking decision demonstrate a sense of ownership and commitment public village tour bromonilan , implementation activity increase skills in manage village tour bromonilan , monitoring evaluation village tour bromonilan support and have utilized in a way effective and efficient will but in source Power man village tour bromonilan Still not enough adequate as well as utilization results village tour bromonilan can give for the Community in Bromonilan Village Sleman Regency